Association of Cardiovascular Disease with Micro Albuminuria in Type 2 Diabetes Mellitus - Study in A Tertiary Care Hospital - Haque, Md Jahirul; Islam, Md Nazrul; Aziz, Md Zakaria Al; Ashrafuzzaman, Shah Mohammad; Banik, Gobindo Chandra; Rahman, AKM Sajedur; Biswas, Sarmistha; Ahasan, HAM Nazmul (Journal of Medicine, 2020)
Introduction: Microalbuminuria appears to be the earliest sign and predictor of the subsequent diabetic renal disease and is a marker of increased cardiovascular morbidity and mortality. It is also a predictor of morbidity and mortality in patients who do not have evidence of significant renal disease Objective: To evaluate the association of microalbuminuria in type 2 DM with cardiovascular diseases and to correlate microalbuminuria with age of onset in type 2 diabetes mellitus. Materials and Method: A hospital based observational study was carried out in the Department of Medicine, Dhaka Medical College & Hospital,Dhaka, from January 2014 to November 2014. A total of 100 patients diagnosed as type 2 diabetes mellitus according to American Diabetic Association guideline were included in this study. Association of microalbuminuria with cardiovascular diseases was determined by statistical analysis and regression analysis. Results: The majority (40.0%) of patients were in 5th decade and the mean (±SD) age was 57.17±11.2 years. According to BMI it is observed that majority of patients were obese in both groups, where male 66.0% and female 75.5%.The occurrence of cardiovascular diseases in type 2 diabetes mellitus patients is increasing with duration of DM, where 61.9% found in newly diagnosed DM. It was observed that 38(38.0%) patients had normoalbuminuria (<30 mg/gm), their mean ACR was 17.6±8.1 mg/gm and 62(62.0%) patients had microalbuminuria (30-300 mg/gm), their mean ACR was 158.7±88.3 mg/gm. Microalbuminuria was found 53(67.1%) and 9(42.9%) patients with cardiovascular diseases and without cardiovascular diseases respectively. Occurrence of microalbuminuia was found significantly higher (p<0.05) in type 2 DM patients with cardiovascular diseases. Conclusion:Microalbuminuria is found strongly associated with cardiovascular diseases in type 2 diabetes mellitus patients and there is 2.72 times more chance of developing cardiovascular diseases. J MEDICINE JUL 2020; 21 (2) : 76-81